WAYS TO DEVELOP THE QUALITIES OF CREATIVITY IN FUTURE EDUCATORS - Meliboyeva Nodira Khatamovna (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the methods of directing future pedagogues’ personal abilities, natural and social energy to quality and effective organization of professional activities are described in detail.